EFEKTIVITAS MEDIA GARISMATIKA UNTUK MENINGKATKAN KEMAMPUAN OPERASI PERKALIAN PADA ANAK LOW VISION KELAS V DI SLB A PAYAKUMBUH - Meliana Siagian; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2015)
AbstractAbstract:  This  research  was  conducted due  to  the  problems found in  the  field indicating that a student with low vision named X in class V of SLB A Payakumbuh got difficulties to complete multiplication items of tens to tens correctly. The purpose of this research  was to  prove the  effectiveness of “garismatika” to  enhance the multiplication ability.This was an experimental research which used Single Subject Research (SSR) method and A-B-A design. Based on these results, it was concluded that the use of “garismatika” was effective to enhance the ability of the student with low vision to multiply tens to tens numbers.